Impact of climate change and Quaternary tectonic uplift on the development of terraces, Kâhta and Göksu creeks, Adıyaman (SE Türkiye) - Sunkar, Murat; Karataş, Zeynel; Çelik, Hasan (Türk Coğrafya Kurumu, 2025)
In this study, optically stimulated luminescence (OSL) dating of terraces formed by the Kâhta and Göksu streams, which are located in the Adıyaman Basin and are not flooded by Atatürk Dam Lake, was completed for the first time. The rate of uplift along with the effect of climate change on the formation of these terraces were revealed, so a definite scientific contribution was made to the dating of uplift in the region. The streams, the most important tributaries of the Euphrates River, are fed from the Southeastern Taurus Mountains. The data in this study clearly supported that the terraces in the study area are present in similar river basins on the south side of the entire Southeast Anatolian Thrust and similar uplift was seen in these areas. This region continued to rise in the Late Pleistocene-Present time interval. From field studies, 5 terrace systems were identified in the Kâhta and Göksu Stream valleys at different elevations. The samples taken from the terraces were dated by the OSL method and the stages of erosion and accumulation were determined. Accordingly, the Kâhta Stream terraces formed 128.53k, 37.31k, 20.13k, 9.69k, 5.36k years ago, respectively, and the Göksu Stream terraces formed 83.45k, 31.43k, 19.58k, 13.27k, 7.94k years ago, respectively. The effect of climate change is evident in the formation of T1 and T3 terraces and their incision by the streams. In addition, the reason why the terraces to the north are located 50 m higher than those to the south is tectonic uplift due to southward thrusts in the Eastern Taurus Orogenic Belt. In light of these data, the tectonic uplift rate for the study area and its immediate surroundings is 0.5 mm/yr

Bu çalışmada, Adıyaman Havzası'nda yer alan ve Atatürk Baraj Gölü'nün altında kalmayan Kâhta ve Göksu derelerinin oluşturduğu terasların optik uyarılmış lüminesans (OSL) tarihlemesi ilk kez tamamlanmıştır. Bu terasların oluşumunda yükselme hızı ve iklim değişikliğinin etkisi ortaya konulmuş, böylece bölgedeki yükselmenin tarihlenmesine kesin bilimsel katkı sağlanmıştır. Bu çalışmadaki veriler, çalışma alanındaki terasların tüm Güneydoğu Anadolu İtkisi'nin güney yakasındaki benzer akarsu havzalarında bulunduğunu ve benzer yükselmenin bu alanlarda görüldüğünü açıkça desteklemektedir. Bu bölge Geç Pleyistosen-Günümüz zaman aralığında yükselmeye devam etmiştir. Arazi çalışmalarından Kâhta ve Göksu Çayı vadilerinde farklı kotlarda 5 adet teras sistemi tespit edilmiştir. Teraslardan alınan örnekler OSL yöntemi ile tarihlendirilmiş ve aşınma ve birikme aşamaları belirlenmiştir. Buna göre Kâhta Çayı terasları sırasıyla 128.53k, 37.31k, 20.13k, 9.69k, 5.36k yıl önce, Göksu Çayı terasları ise sırasıyla 83.45k, 31.43k, 19.58k, 13.27k, 7.94k yıl önce oluşmuştur. T1 ve T3 teraslarının oluşumunda ve akarsular tarafından kesilmesinde iklim değişikliğinin etkisi belirgindir. Ayrıca kuzeydeki terasların güneydekilerden 50 m daha yüksekte yer almasının nedeni Doğu Toros Orojenik Kuşağı'nda güneye doğru itilmeler sonucu oluşan tektonik yükselmedir. Bu veriler ışığında çalışma alanı ve yakın çevresi için tektonik yükselme hızı 0,5 mm/yıl olarak hesaplanmıştır.
Kâhta ve Göksu Çayı Taraçalarının OSL Yaşlandırması ve Taraçaların Gelişiminde İklim Değişmeleri ve Tektonik Hareketlerin Etkisi (Güneydoğu Türkiye/Adıyaman)
Keywords: Quaternary Environments; Kuaterner Ortamlar